Master Final Project - Business Plan of Style_We_Knit - Pok, Yan Kei; Leung, Hiu Yan (My University, 2020)
Style_We_Knit is a fashion brand that offers hand knitting DIY (Do It Yourself) kits consisting of well-written patterns and materials needed, such as yarns, needles, and accessories, so that customers can indulge in the joy of creating their own clothing and at the same time, contribute to a more sustainable environment of fashion. We target young women markets in Hong Kong and hope to encourage people choosing sustainable clothing over fast fashion by providing solutions of creative garment production. We offer practical and easy-to-follow tools for customers to play their parts in a more sustainable fashion world by selling DIY packages on e-commerce platforms including a brand website. By advertising on social platforms such as Facebook and Instagram, and running online shops on third-party platforms including Etsy and Crecra, we attract the general audience and ideally convert them into potential customers.
Keywords: e-commerce; start-up business; online shop; business plan; Máster Universitario en Dirección y Administración de Empresas (MBA)